College internships, tenure gaps, and student outcomes: a multiple-treatment matching approach. Issue 4 (4th July 2019) - Wesley Routon, P.; Walker, Jay K.
ABSTRACT: College internships are popular and often promoted. Quantifying their impacts is difficult as students often take time away from classes to participate. We implement multiple-treatment propensity score matching to untangle the simultaneous effects of internships and discontinuous college tenure. Using a sample of over 442, 000 students from 619 US institutions, we estimate their on academic performance, human and social capital gains, college satisfaction, and post-graduation goals. Many of the benefits of internships would be underestimated if discontinuous college tenure were unaccounted for. In other words, students completing an internship without a break from classes are more changed by their experience.